Serum Anti-oligodendrocyte Autoantibodies in Patients With Multiple Sclerosis Detected by a Tissue-Based Immunofluorescence Assay - Miyachi, Yukino; Fujii, Takayuki; Yamasaki, Ryo; Tsuchimoto, Daisuke; Iinuma, Kyoko; Sakoda, Ayako; Fukumoto, Shoko; Matsushita, Takuya; Masaki, Katsuhisa; Isobe, Noriko; Nakabeppu, Yusaku; Kira, Jun-ichi (Frontiers in Neurology, 2021)
Multiple sclerosis (MS), the most prevalent inflammatory disease of the central nervous system (CNS), is characterized by damaged to myelin sheaths and oligodendrocytes. Because MS patients have variable clinical courses and disease severities, it is important to identify biomarkers that predict disease activity and severity. In this study, we assessed the frequencies of serum autoantibodies against mature oligodendrocytes in MS patients using a tissue-based immunofluorescence assay (IFA) to determine whether anti-oligodendrocyte antibodies are associated with the clinical features of MS patients and whether they might be a biomarker to assess CNS tissue damage in MS patients. We assessed the binding of serum autoantibodies to mouse oligodendrocytes expressing Nogo-A, a reliable mature oligodendrocyte marker, by IFA with mouse brain and sera from 147 MS patients, comprising 103 relapsing–remitting MS (RRMS), 22 secondary progressive MS (SPMS), and 22 primary progressive MS (PPMS) patients, 38 neuromyelitis optica spectrum disorder (NMOSD) patients, 23 other inflammatory neurological disorder (OIND) patients, and 39 healthy controls (HCs). Western blotting (WB) was performed using extracted mouse cerebellum proteins and IgG from anti-oligodendrocyte antibody-positive MS patients. Tissue-based IFA showed that anti-oligodendrocyte antibodies were positive in 3/22 (13.6%) PPMS and 1/22 (4.5%) SPMS patients but not in RRMS, NMOSD, and OIND patients or HCs. WB demonstrated the target CNS proteins recognized by serum anti-oligodendrocyte antibodies were approximately 110 kDa and/or 150 kDa. Compared with anti-oligodendrocyte antibody-negative MS patients, MS patients with anti-oligodendrocyte antibodies were significantly older at the time of serum sampling, scored significantly higher on the Expanded Disability Status Scale and the Multiple Sclerosis Severity Score, and had a higher frequency of mental disturbance. Although the clinical significance of anti-oligodendrocyte antibodies is still unclear because of their low frequency, anti-oligodendrocyte autoantibodies are potential biomarkers for monitoring the disease pathology and progression in MS.